The safeguard of liberty and property : the Supreme Court, Kelo v. New London, and the takings clause / Guy F. Burnett. - Burnett, Guy F., 1979- (Lexington Books, 2015)
This book is an in-depth analysis of the case law and popular backlash to the Supreme Court case Kelo v. New London (2005). Using a variety of legal, academic, legislative, media, and popular sources, it examines and establishes the Court's most recent interpretation of property rights, eminent domain, and popular reaction to the interpretation.